Religious and Spiritual Tourism: From Its Origins to Alentejo (Portugal) - Sousa, Bruno (2020)
Over the years there has been an increase in competition among tourism destinations, leading to the need for a deeper understanding about the tourism realm, impact, and management. Tourism has expanded its scope, reflecting an increasing recognition in the academic community paralleled by the application of interdisciplinary concepts and methods. Indeed, research in tourism has been studying its various implications from a multitude of perspectives and with interdisciplinary insights. Areas in tourism research entail planning of tourism destinations, local development, environmental impact, territorial brand management, and tourist loyalty. With new motivations, new niches are created, and it is one of those niches that the authors address in this work, namely, spiritual tourism. Spiritual tourism derives from religious tourism because it is linked to spiritualism and is associated with wellness tourism. This manuscript aims to present the importance of spirituality in the context of tourism (Alentejo, Portugal). In the end, new lines of research will be presented for the future.